Protecting human security in Africa - Abass, Ademola (Oxford : Oxford University Press, 2010)
This text explores the gravest threats to human security in Africa. Written by leading experts on its various themes, it combines legal and policy perspectives on the issues, making it an indispensable book for those seeking to learn more about the real challenges facing Africans and African organizations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human security -- Africa; Human rights -- Africa; Africa -- Social policy; Africa -- Social conditions -- 21st century